SACCARIN: KEKUATAN MEDIA DALAM PERGESERAN POLA HIDUP (Kajian Teori Peluru pada Fenomena Pemanis Buatan) - Adiella Yankie Lubis (Jurnal Komunikasi dan Bisnis, 2017)
Artificial sweeteners was flarely used as a substitute for pure sweetener in the era of the first world war in the United States, not a few people who do not know the use of chemicals in the artificial sweetener used in some canned beverage product of its time. This study is a theoretical study of theory, where bullet theory will be used to see the saccarin phenomenon, and then associate it with the theory of media that had a view of the absolute effect of the mass media to illustrate the construction of a healthy lifestyle by using artificial sugar substitutes products through the illusion of control on the use of artificial sugar without heeding the dangers of artificial sweeteners and such products.